Financial crisis in the Cyprus Republic - Iordanidou, Sofia (Javnost (Ljubljana), 2014)
For long, the inter-communal conflict between Greek Cypriots and Turkish Cypriot as well as the invasion and occupation of North Cyprus by Turkey defined the Cyprus Issue/Problem which has affected both the reality and image of Cyprus. The more recent financial crisis has proved to be a mega event that also has the capacity to redefine both the reality and image of Cyprus. This paper aims to address key political and discursive aspects of the financial crisis and their specific expression in Cyprus. A focal point of the analysis is the displacement of the Cyprus Issue by the financial crisis as the dominant factor affecting domestic politics, political rhetoric and international image of the Cyprus Republic. The paper draws together and builds on insights from a number of separate but complementary research projects addressing different facets of the public communication of the financial crisis in Cyprus. The second part provides an account of the unfolding of the financial crisis in Cyprus and some of its major implications; the third examines the impact of the financial crisis upon Cyprus politics and more particularly the displacement of the Cyprus Issue by the Financial Crisis as key issue in the campaign agenda. The fourth part examines the domestic political rhetoric employed for the crisis in Cyprus and more specifically the rhetoric of fear. The fifth part examines the image of Cyprus constructed by the politics of blame, not least in the German political discourse and the sixth part considers the international image of Cyprus.
Keywords: Ciper; ekonomska kriza; ekonomska politika; ekonomski položaj; politične razmere; mass media; množični mediji